Fairness and support for redistribution: The role of preferences and beliefs - Sören Harrs; Maj-Britt Sterba (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2025)
This paper establishes three novel findings on fairness and redistribution by combining theory-driven experimental games with large-scale surveys in the U.S. and five European countries. First, individuals revealing egalitarian, libertarian, or meritocratic fairness preferences in experimental games show large differences in support for tax and transfer policies. Second, beliefs in merit strongly predict policy support among meritocrats, but are less predictive among non-meritocrats. Third, fairness concerns matter across income groups and political camps. Our findings challenge the assumptions that meritocratic preferences are homogeneous, that fairness is a luxury good, and that fairness is mainly a moral foundation of left voters.
urn:nbn:de:bsz:352-2-10xhazwndaox66
Keywords: D31; D63; H24; 320; Fairness; Redistribution; Political Ideology; Moral Foundations